Ionic liquid-mediated hexagonally porous ZnO nanocrystal-supported Au catalysts: highly stable materials for aldehyde oxidative esterification. Issue 2 (30th November 2022) - Zheng, Yanxia; Yang, Lixi; Chen, Yao; Yang, Yubo; Zuo, Cuncun; An, Jiutao; Wang, Qian; Huang, Haofei; Li, Yuchao; Wang, Ming
Abstract : Ionic liquid-mediated hexagonally porous ZnO nanocrystal-supported Au catalysts: highly efficient and stable materials for oxidative esterification of methylacrolein. Abstract : ZnO nanorods with hexagonal pores have been synthesized by the hydrothermal method assisted by ionic liquids (ILs) with different alkyl chain lengths (C6 mimCl, C10 mimCl and C14 mimCl). Then Au nanoparticles were supported on the corresponding ZnO by deposition–precipitation (DP) and applied for oxidative esterification of methacrolein (MAL) with methanol to methyl methacrylate (MMA). The hexagonal pore structure was confirmed by TEM. A relationship between ZnO's base/reduction capacity ratio, calculated from CO2 -TPD/H2 -TPR data, and the catalytic performance for preparing MMA was found for Au/ZnO catalysts. The Au nanoparticles supported on porous zinc oxide prepared by C10 mimCl with a predominance of basic sites and active oxygen species on the catalyst surface exhibited the best activity. The Mars–van Krevelen reaction mechanism occurred on the surface of the Au/ZnO-IL catalyst, which was enhanced by extensive vacancy defects, and the strong interaction between Au and ZnO-C10 according to the results of XPS and in situ DRIFTS analyses. Compared to the easy aggregation of Au nanoparticles on commercial ZnO, the Au/ZnO-IL catalysts retained high activity after reaction for 14 recycling runs, and the increasing size and leaching of Au particles were not observed due to the additional pore structure.